1999
DOI: 10.1110/ps.8.12.2751
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the kinetics of S‐S bond, secondary structure, and active site formation during refolding of reduced denatured hen egg white lysozyme

Abstract: To investigate the role of some tertiary interactions, the disulfide bonds, in the early stages of refolding of hen lysozyme, we report the kinetics of reoxidation of denatured and reduced lysozyme under the same refolding conditions as those previously used to investigate the kinetics of regain of its circular dichroism~CD!, fluorescence, and activity. At different stages of the refolding, the oxidation of the protein was blocked by alkylation of the free cysteines with iodoacetamide and the various oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 36 publications
3
23
0
Order By: Relevance
“…Without mutations, the formation of fibrillar aggregates of wild‐type CEWL under native conditions is generally impossible, because the native state of CEWL is quite stable with a conformational stability of 10.2 kCal/mol 48. Structural studies have highlighted the importance of these disulfide bonds to the stability of native structure of CEWL 49, 50. Here, we applied controlled UV doses to CEWL to selectively disrupt its terminal disulfide bonds and make its conformational states accessible from native state through thermal fluctuation under native condition.…”
Section: Introductionmentioning
confidence: 99%
“…Without mutations, the formation of fibrillar aggregates of wild‐type CEWL under native conditions is generally impossible, because the native state of CEWL is quite stable with a conformational stability of 10.2 kCal/mol 48. Structural studies have highlighted the importance of these disulfide bonds to the stability of native structure of CEWL 49, 50. Here, we applied controlled UV doses to CEWL to selectively disrupt its terminal disulfide bonds and make its conformational states accessible from native state through thermal fluctuation under native condition.…”
Section: Introductionmentioning
confidence: 99%
“…Till now, the oxidative folding of lysozyme has been well studied, including its disulfide folding pathway [14][15][16] and folding kinetics [17][18][19][20][21]. However, these studies revealed little about what are the rate determinants of different phases.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] Accordingly, genetically engineered disulfide bonds have been used successfully as a tool to probe nucleation sites of the protein folding process. 5,[15][16][17] Additionally, a number of studies dealt with the formation of disulfide bridges within the folding process. [18][19][20][21][22] However, the influence of naturally occurring disulfide bridges on the mechanism of a protein folding reaction is still not completely understood even though theoretical considerations suggest it to be of pronounced importance.…”
Section: Introductionmentioning
confidence: 99%